2023
DOI: 10.1177/15271544231182586
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Against Nurses: Challenges and Solutions for Europe

Abstract: We report the results of a mapping exercise by the European Federation of Nurses (EFN) on challenges and solutions related to violence against nurses. This is an issue of growing international concern, with the problem accentuated during and following the COVID-19 pandemic. Following a cross-sectional observational design, an online questionnaire was distributed among 35 national nurses’ associations across Europe in March 2021. Face validity was achieved through an expert panel. Descriptive statistics were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our study showed that nurses in critical care units are exposed to workplace abuse; 62.5% of them had experienced at least one incident in the past year. This is not a surprising finding, because other authors have obtained similar data [18][19][20][21][22][23]. In their study, Cheraghi et al found that 74.1% of nurses had been exposed to some form of abuse similar to the results from our study [18].…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that nurses in critical care units are exposed to workplace abuse; 62.5% of them had experienced at least one incident in the past year. This is not a surprising finding, because other authors have obtained similar data [18][19][20][21][22][23]. In their study, Cheraghi et al found that 74.1% of nurses had been exposed to some form of abuse similar to the results from our study [18].…”
Section: Discussionsupporting
confidence: 90%
“…Workplace violence against personal care workers results in physical and psychological damage at individual levels and has a considerable impact on the delivery of health care services (i.e., leads to poor quality of care delivered, increased absenteeism, and health workers' decision to leave the field) [23]. Therefore, dealing with workplace violence must be integrated into the functions of organizations rather than being made the responsibility of individual workers.…”
Section: Discussionmentioning
confidence: 99%
“…Violence experienced by care workers can negatively affect their physical and psychological well-being and job-related variables (i.e., job satisfaction and burnout). These negative aspects may lead to a lower quality of patient care and indicate the absence of appropriate laws and legislation dealing with safe working environments [23]. However, there is currently no research comparing the extent of physical assault experienced by personal care workers to that experienced by workers in other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The study results also confirmed the earlier literature [ 25 ], where gender discrimination was a significant reason for creating workplace person-related hostility among nurses and building their intention to leave the organization. [ 64 ] found that nurses experience discrimination and gender-based hostility from other healthcare professionals at different ranks that adversely affect their health and retention. Lack of social and political power, weak position in an organizational hierarchy, and subordination by other professions were the main contributing factors to discrimination against nurses.…”
Section: Discussionmentioning
confidence: 99%